Spiritualism and psychodrama - Seda Bonilla, Eduardo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The similarities between the structural patterns of a spiritualist session and psychodrama are described from a theoretical viewpoint. An account of a spiritualist session with a patient who had been in a catatonic-like state for three days is presented. This session is then analyzed in psychoanalytic terms.